An Immunologic Compatibility Testing Was Not Useful for Donor Selection in Fecal Microbiota Transplantation for Ulcerative Colitis - Ponce-Alonso, Manuel; García-Hoz, Carlota; Halperin, Ana; Nuño, Javier; Nicolás, Pilar; Martínez-Pérez, Adolfo; Ocaña, Juan; García-Pérez, Juan Carlos; Guerrero, Antonio; López-Sanromán, Antonio; Cantón, Rafael; Roy, Garbiñe; et al. (Frontiers in Immunology, 2021)
Fecal microbiota transplantation (FMT) is an effective procedure against Clostridioides difficile infection (CDI), with promising but still suboptimal performance in other diseases, such as ulcerative colitis (UC). The recipient’s mucosal immune response against the donor’s microbiota could be relevant factor in the effectiveness of FMT. Our aim was to design and validate an individualized immune-based test to optimize the fecal donor selection for FMT. First, we performed an in vitro validation of the test by co-culturing lymphocytes obtained from the small intestine mucosa of organ donor cadavers (n=7) and microbe-associated molecular patterns (MAMPs) obtained from the feces of 19 healthy donors. The inflammatory response was determined by interleukin supernatant quantification using the Cytometric Bead Array kit (B&D). We then conducted a clinical pilot study with 4 patients with UC using immunocompetent cells extracted from rectal biopsies and MAMPs from 3 donor candidates. We employed the test results to guide donor selection for FMT, which was performed by colonoscopy followed by 4 booster instillations by enema in the following month. The microbiome engraftment was assessed by 16S rDNA massive sequencing in feces, and the patients were clinically followed-up for 16 weeks. The results demonstrated that IL-6, IL-8, and IL-1ß were the most variable markers, although we observed a general tolerance to the microbial insults. Clinical and colonoscopy remission of the patients with UC was not achieved after 16 weeks, although FMT provoked enrichment of the Bacteroidota phylum and Prevotella genus, with a decrease in the Actinobacteriota phylum and Agathobacter genus. The most relevant result was the lack of Akkermansia engraftment in UC. In summary, the clinical success of FMT in patients with UC appears not to be influenced by donor selection based on the explored recipient’s local immunological response to FMT, suggesting that this approach would not be valid for FMT fecal donor optimization in such patients.